Decolonising from London. An Indian psychogeography around Victorian railway spaces (1870-1914) - Arup K. Chatterjee (Diasporas: Circulations, Migrations, Histoire)
While the expansion of the London Underground coincided with that of the Indian Railways, an Indian psychogeography was quietly emerging in the marginal geographies of the Victorian imperial capital. In their memoirs, Pothum Ragaviah, Mukharji, Jang, Malabari, Pillai and Pandian, among other Indian travellers, engaged with London’s railway spaces to renegotiate their colonial subjectivity. As London neighbourhoods assumed an Asiatic character, Indian memoirists inhabited London in a typographical imagination, or Typogravia. Architectural, economic, artistic and literary consciousness overlapped in this typographical space to foreground independent Indian aesthetics of travelling and selfhood, shaped around London’s railway spaces.